Effect of E-SAMSAT on Motor Vehicle Taxpayer Compliance in Makassar City - Ainun Ratifa Rasyid (JEKAMI Journal of Accounting, 2023)
The purpose of this study is a type of quantitative research with the aim of knowing the effect of E-SAMSAT on motor vehicle taxpayer compliance at the SAMSAT office of the Makassar Regional Revenue UPT 1. The population that is the object of research is the entire Makassar Regional Revenue UPT office. 126 people were taken by purposive random sampling technique. The type of data used in this study is quantitative data obtained from questionnaires distributed and related to the problem under study. Data was collected by distributing questionnaires. In this study the data sources used in data collection include primary data and secondary data. The research instrument used in this study used the Likert scale method. The data analysis technique in this research is instrument test, simple linear regression analysis and hypothesis testing. Based on the results of data research using statistical calculations through the Statistical package for the Social Science (SPPS) version 25 application regarding the effect of E-SAMSAT on motor vehicle tax compliance at the SAMSAT office of UPT Revenue Makassar Region 1 which has been discussed from the previous chapter, the authors draw The important conclusion is that it shows that E-SAMSAT has a positive and significant effect on taxpayer compliance.